A case report on ischemic Mitral regurgitation (World Journal of Current Medical and Pharmaceutical Research, 2023)
Ischemic Mitral regurgitation is a leakage of blood backward through the mitral valve each time the left ventricle contraction. Patients are often ill with significant hemodynamic instability (Acute) needs urgent medical treatment. During normal cycle mitral valve (bicuspid valve) opens and closes normally. But in mitral regurgitation mitral valve does not opens and closes properly. The blood  from right atrium moves to right ventricle then mitral valve does not closes properly leads to blood ejected back to right atrium which results in pulmonary edema and increases pulmonary hypertension. Ischemic Mitral regurgitation leads to complication of acute myocardial infraction and coronary artery disease